2020
DOI: 10.1080/22221751.2020.1829082
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the endolysosomal host-SARS-CoV-2 interface by clinically licensed functional inhibitors of acid sphingomyelinase (FIASMA) including the antidepressant fluoxetine

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic caused by the Severe Acute Respiratory Syndrome Related Coronavirus 2 (SARS-CoV-2) is a global health emergency. As only very limited therapeutic options are clinically available, there is an urgent need for the rapid development of safe, effective, and globally available pharmaceuticals that inhibit SARS-CoV-2 entry and ameliorate COVID-19 severity. In this study, we explored the use of small compounds acting on the homeostasis of the endolysosomal host-pathoge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
198
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(222 citation statements)
references
References 46 publications
(80 reference statements)
18
198
1
Order By: Relevance
“…Moreover, SARS-CoV-2 specifically interacts with tyrosine-protein kinase receptor UFO (Axl) on the host membrane, where this receptor can promote viral entry [ 13 ], as already described for EBOV ( Figure 1 A,B). Interestingly and also previously reported for EBOV, fluoxetine, a functional inhibitor of ASMase, efficiently abrogates the SARS-CoV-2 entry and propagation in Vero E6 and CaLu-3 cells, suggesting that ASMase may also play a significant role in the early steps of the virus infection cycle [ 3 , 14 ]. A further understanding of the role of attachment factors implicated in SARS-CoV-2 binding will be required to reduce systemic dissemination between susceptible cells and tissues.…”
Section: Setting the Stage For Infection: Viral Binding And Host Asupporting
confidence: 63%
“…Moreover, SARS-CoV-2 specifically interacts with tyrosine-protein kinase receptor UFO (Axl) on the host membrane, where this receptor can promote viral entry [ 13 ], as already described for EBOV ( Figure 1 A,B). Interestingly and also previously reported for EBOV, fluoxetine, a functional inhibitor of ASMase, efficiently abrogates the SARS-CoV-2 entry and propagation in Vero E6 and CaLu-3 cells, suggesting that ASMase may also play a significant role in the early steps of the virus infection cycle [ 3 , 14 ]. A further understanding of the role of attachment factors implicated in SARS-CoV-2 binding will be required to reduce systemic dissemination between susceptible cells and tissues.…”
Section: Setting the Stage For Infection: Viral Binding And Host Asupporting
confidence: 63%
“…Cationic and amphiphilic represent key physicochemical characteristics of a newly proposed classification of drugs related to their ability of acid sphingomyelinase (ASM) inhibition and called Functional Inhibitors of Acid SphingoMyelinase (FIASMAs) [ 7 ],. This property could also be linked to the endolysosomal anti-SARS-CoV-2 activity and of the 11 drugs described above, 7 are indeed confirmed FIASMAs [ 6 , 8 , 9 ].…”
Section: Pharmacochemical Based Hypothesismentioning
confidence: 66%
“…Comparing the Hoertel et al and Zimniak et al publications, Hoertel et al found that in addition to fluoxetine, venlafaxine (median dose of 75mg) and escitalopram (median dose of 10mg) were also associated with a lower risk of intubation and death, however, Zimniak et al showed neither SSRIs escitalopram nor paroxetine inhibited SARS-Cov-2 in vitro (Hoertel et al, 2020;Zimniak et al, 2020). Of note, as shown in Table 1, a 40mg or 60mg daily fluoxetine dose results in 90% inhibition of the SARS-Cov-2 infection due to surpassing the EC90 value of 4.02 μM as found in Calu-3 cells and the EC90 value of 1.81 μM in Vero E6 cells (Schloer et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, Zimniak et al reported that following a 3-day incubation period of fluoxetine in Vero cells, inoculated at a multiplicity of infection (MOI) of 0.5, resulted in the median maximal effective concentration (EC50) of 387 ng/ml (1.1 μM) and further found a concentration of 800 ng/ml (2.3 μM) significantly inhibited SARS-Cov-2 replication (Zimniak et al, 2020). Similarly, Schloer et al found that fluoxetine significantly decreases SARS-Cov-2 titers, after a 48-hour incubation period, in both African green monkey kidney epithelial Vero E6 cells (EC50 = 0.69 μM and 90% maximal effective concentration [EC90] = 1.81 μM, MOI=0.01) and human-lung Calu-3 cells (EC50 = 0.82 μM and EC90 = 4.02 μM, MOI=0.1) (Schloer et al, 2020). Taken together, these in vitro studies prove in a dose-dependent manner, the SSRI fluoxetine inhibits the SARS-CoV-2 pathogen known to cause the worldwide pandemic, the novel coronavirus disease 2019 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation